An imaging system with a large depth of field based on an overlapped micro-lens array. Issue 1 (2016) - Pang, Kuo; Song, Le; Fang, Fengzhou; Zhang, Yue; Zhang, Haoyang
Abstract: An overlapped micro-lens array containing 222, 762 lenslets is proposed and designed to increase the utilization of image sensors in light field imaging systems. The array is made by micro-injection moulding, and the mould is processed by ultra-precision milling to achieve high precision and a low manufacturing cost. To obtain a compact configuration of each image under a micro-lens, a customized square aperture is introduced into the light path. The experiment shows that compared with the conventional design, the overlapped micro-lens array has improved the fill factor from π /4 to 1, which largely increases the utilization of the image sensors.